THE IMPACT OF THE STREET VENDOR RELOCATION POLICY ON LOSARI BEACH, MAKASSAR CITY - Zal-Zabila, Nurul Wahida; Akib, Haedar; Guntur, Muhammad (Universitas Negeri Makassar, 2025)
This study aims to determine the impact of the street vendor relocation policy on Losari Beach, Makassar City. This study uses a qualitative approach with a descriptive method. Data collection was carried out through field observations, interviews, documentation and literature studies. Data analysis techniques used data condensation, data presentation and drawing conclusions. The results of this study indicate that the Impact of the Street Vendor Relocation Policy on Losari Beach, Makassar City has a good impact. Based on the four indicators of the theory put forward by Samodra Wibawa (1994) on the impact of the policy, it is known that the three indicators are included in the category of having a good impact. These indicators are organizational impact, impact on society, and impact on institutions and social systems, while the individual impact indicator has a less good impact on the street vendor relocation policy on Losari Beach, Makassar City.